2004
DOI: 10.1084/jem.20031435
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin-specific CD8+ T Cell Responses Provide Evidence of In Vivo Cross-Priming by Antigen-Presenting Cells in Vaccinated Pancreatic Cancer Patients

Abstract: Tumor-specific CD8+ T cells can potentially be activated by two distinct mechanisms of major histocompatibility complex class I–restricted antigen presentation as follows: direct presentation by tumor cells themselves or indirect presentation by professional antigen-presenting cells (APCs). However, controversy still exists as to whether indirect presentation (the cross-priming mechanism) can contribute to effective in vivo priming of tumor-specific CD8+ T cells that are capable of eradicating cancer in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
247
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(249 citation statements)
references
References 52 publications
(97 reference statements)
2
247
0
Order By: Relevance
“…The heightened vaccine-based antitumor immune response in irradiated hosts was associated with tumor regression and prolonged survival of mice. It had previously been thought that some cytotoxic agents, such as cyclophosphamide, might enhance the efficacy of adoptively transferred immunotherapy by augmenting the engraftment of adoptively transferred tumor-reactive effector T cells, [11][12][13] possibly by creating space. 1, 14 However, in our study, vaccination after irradiation without adoptive transfer yielded similar results, indicating that a self-reconstituted host immune system is reliable for antigen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The heightened vaccine-based antitumor immune response in irradiated hosts was associated with tumor regression and prolonged survival of mice. It had previously been thought that some cytotoxic agents, such as cyclophosphamide, might enhance the efficacy of adoptively transferred immunotherapy by augmenting the engraftment of adoptively transferred tumor-reactive effector T cells, [11][12][13] possibly by creating space. 1, 14 However, in our study, vaccination after irradiation without adoptive transfer yielded similar results, indicating that a self-reconstituted host immune system is reliable for antigen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentation in BM chimeric mice with differential expression of antigen-presenting molecules and in humans vaccinated with allogeneic tumor cells has demonstrated that the ability to cross-present cell-associated antigens is restricted to BM-derived APC [24,25]. Several groups have investigated the identity of the BM-derived APC involved in MHC class I-restricted presentation of exogenous antigens.…”
Section: Introductionmentioning
confidence: 99%
“…It is still unresolved whether cross-presentation or direct presentation is the relevant mechanism governing tumor immunity [20,21]. Although some studies have suggested that the two processes act as redundant non-mutually exclusive mechanisms [22], other authors have proposed cross-presentation to be the major mechanism for the activation of naïve CD8 1 T cells [23].Experimentation in BM chimeric mice with differential expression of antigen-presenting molecules and in humans vaccinated with allogeneic tumor cells has demonstrated that the ability to cross-present cell-associated antigens is restricted to BM-derived APC [24,25]. Several groups have investigated the identity of the BM-derived APC involved in MHC class I-restricted presentation of exogenous antigens.…”
mentioning
confidence: 99%
“…Yet another toxin insertion approach used a a biodegradable nanoparticulate delivery system targeted specifically to mesothelin-overxpressing cell lines to deliver diphtheria toxin DNA, which effectively inhibited protein translation of targeted cells in vitro 38 . specific CD4 + and CD8 + T cells were generated from peripheral blood lymphocytes of 50% of patients with pancreatic cancer, up from only 20% of healthy individuals 27 , and another study showed consistent induction of CD8 + T cell responses to multiple MSLN epitopes in a small number of patients 40 . A study by Yokokawa et al sought to define additional MSLN epitotpes capable of more efficiently activating T cells to lyse tumors 10 .…”
Section: Advances In Diagnosis and Treatment Of Mesothelin-overexpresmentioning
confidence: 96%